Transformation of Marriage Dowry into Shares in a Limited Liability Company: A Review of Civil Law and its Implications - Latupono, Barzah (Journal of Ecohumanism, 2024)
The transformation of marital dowry into shares in a Limited Liability Company marks a significant shift in the paradigm of civil and business law in Indonesia. This research explores the legal basis that enables the transformation of dowry into shares and its legal and business implications. In Islamic law in Indonesia, dowry is an obligatory gift from the prospective husband to the prospective wife which is the full right of the wife, and can be in the form of shares as per Clauses 32 of the Compilation of Islamic Law. The legal framework governing shares in Limited Liability Companies, including Clauses 48 point (1) and Clauses 52 of Law point 40 of 2007 on Limited Liability Companies, emphasizes the importance of proof of share ownership and the rights of shareholders. A normative juridical approach with qualitative analysis of legal documents and jurisprudence is used in this research. The results show that transforming dowry into shares has a strong legal basis and provides long-term financial benefits and education on share investment. However, fluctuations in share value and management risks remain a challenge. The case study shows that this transformation can inspire people to consider stocks in family financial planning. With in-depth understanding and proper documentation, the transformation of dowry into shares can provide significant financial benefits and maintain legal certainty in marriage.